Komunikasi Sosial EXO-L Indonesia di Akun X - Nurhaipah, Titih; Fahrudin, Atef; Alfadhilah, Alaisya (JIKA (Jurnal Ilmu Komunikasi Andalan), 2024)
This research examines the social communication practices of bilingual members within the EXO-L fandom in Indonesia on the X platform (formerly Twitter), with a focus on the utilization of English slang words. Employing a qualitative research design through virtual ethnography, the study investigates three key objectives: self-concept construction, self-existence assertion, and the development of interpersonal relationships. The findings highlight that English slang words function as a linguistic medium for identity expression, social integration, and solidarity reinforcement. Members demonstrate adaptability in selecting between English slang and formal English to align with social norms while maintaining individual authenticity. The use of shared linguistic features and mutual interest in EXO as a K-Pop idol group facilitates accelerated relationship-building and deepened social bonds. This study provides theoretical contributions to the field of digital communication and popular culture studies, offering insights into the dynamics of virtual communities in a globalized digital era.